2007
DOI: 10.1016/j.brainresrev.2007.06.023
|View full text |Cite
|
Sign up to set email alerts
|

Role of the neural crest in face and brain development

Abstract: Since the time of Ramon y Cajal, very significant progress has been accomplished in our knowledge of the fate of the early neural primordium. The origin of the peripheral nervous system from the transient and pluripotent embryonic structure, the neural crest has been fully deciphered using appropriate cell marking techniques. Most of the pioneer work in this field was carried out in lower vertebrates up to 1950 and later on in the avian embryo. New techniques which allow the genetic labelling of embryonic cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
85
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(85 citation statements)
references
References 48 publications
0
85
0
Order By: Relevance
“…In recent work, we showed that after excision of Shh-expressing anterior foregut endoderm along with the entire forehead at early neurula stages (5-6 ss), the cephalic NCCs which colonize BA1 exiting from the mesencephalon migrated normally but were further on subjected to massive apoptosis, whereas Shh was not expressed in the pharyngeal endoderm. Fgf8 and Bmp4 transcripts were absent in BA1 ectoderm at E3-4 and the embryos were further deprived of Meckel's cartilage and lower jaw (Brito et al, 2006;Le Douarin et al, 2007). These data suggested that the ability of the anterior pharyngeal endoderm to instruct BA1 to form an ectopic lower beak (Couly et al, 2002) might be related to its capacity to produce Shh.…”
Section: Shh Signal Is Pivotal For the Development Of Meckel's Cartilmentioning
confidence: 96%
“…In recent work, we showed that after excision of Shh-expressing anterior foregut endoderm along with the entire forehead at early neurula stages (5-6 ss), the cephalic NCCs which colonize BA1 exiting from the mesencephalon migrated normally but were further on subjected to massive apoptosis, whereas Shh was not expressed in the pharyngeal endoderm. Fgf8 and Bmp4 transcripts were absent in BA1 ectoderm at E3-4 and the embryos were further deprived of Meckel's cartilage and lower jaw (Brito et al, 2006;Le Douarin et al, 2007). These data suggested that the ability of the anterior pharyngeal endoderm to instruct BA1 to form an ectopic lower beak (Couly et al, 2002) might be related to its capacity to produce Shh.…”
Section: Shh Signal Is Pivotal For the Development Of Meckel's Cartilmentioning
confidence: 96%
“…Cranial neural crest cells (CNCCs) emigrate from the caudal forebrain, midbrain and hindbrain to the level of the first somite and give rise to additional cell fates in comparison to trunk NCCs, contributing to cartilage, bone and connective tissue (Le Douarin et al, 2007;Santagati and Rijli, 2003). CNCCs migrate into the branchial arches (BAs), becoming NC-derived mesenchymal progenitor cells (MPCs), which produce cartilage and skeletogenic elements of the craniofacial region.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, cells in BA1 and anterior domains are devoid of Hox gene expression, which allows formation of the chondrogenic and skeletal elements of the facial region (Creuzet et al, 2002;Kanzler et al, 1998;Minoux and Rijli, 2010). In addition to these intrinsic cues, CNCC fates are regulated by environmental signals, such as Tgfβ (Wurdak et al, 2006) and Fgf8 expressed from the facial and BA ectoderm (Le Douarin et al, 2007;Santagati and Rijli, 2003). As a consequence of such signaling, expression of the transcription factor Sox9 is upregulated in MPCs, while expression levels of the NC specifier gene and NC stem cell (NCSC) marker Sox10 decrease (John et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…These cells follow preferentially a subectodermal route, contact the presumptive olfactory ectoderm at Hamburger Hamilton stage 10 (HH10) and remain in its close proximity up to HH18 (Couly and Le Douarin, 1990;Couly et al, 1993;Le Douarin et al, 2007). Then, neural crest-derived chondrogenic ectomesenchyme accumulates within the nasal prominences.…”
Section: Introductionmentioning
confidence: 99%